The Role of 3D Printing in the Manufacturing of Custom - Made Footwear - Narayan, Jay (Journal of Research in Science and Engineering, 2025)
The footwear market went through a revolutionary change due to 3D printing that employs state - of - the - art additive manufacturing to design personalized sustainable and ergonomic footwear products. Digital scanning and novel materials and geometrically optimized shapes utilized in conjunction via this technology provide improved comfort with biomechanical alignment and superior aesthetic features. A descriptive exploratory research design quantified 3D printing impacts on customization as well as durability and consumer attitude among 100 Delhi NCR region participants. The results indicate that customization of footwear leads to highly positive results through 3D printing technology (β = 0.405, p < 0.05) while consumer satisfaction reveals high correlations with product durability (r = 0.594, p < 0.01). Product development coupled with sustainability advantage and financial saving through 3D printing is available, but accessibility barriers and large - scale customization constraints still endure. Individuals recognize tailor - made 3D printing sneakers as a revolutionized custom style since seventy - two percent of surveyed buyers recognize that it increases comfort level while delivering higher athletic performance. The technical procedure has a good environmental consequence as it not only reduces waste material but maximizes resource efficiency too.3D printing proves its increasing significance to footwear industries through the creation of customer - oriented manufacturing techniques which match contemporary market needs.